Social Network Analysis: User Responses to Lazada Marketplace Promotions: Analisis Jaringan Sosial: Respon Pengguna terhadap Promosi di Lazada Marketplace - Meynur Rohmah Ubaidillah; Rita Ambarwati Sukmono (Academia Open, 2023)
This study employs qualitative research methods to measure and map user interactions with marketing promotional content on Lazada Marketplace, focusing on images related to vouchers, cashback offers, and flash sales. Data was collected from Twitter and analyzed using Wordij and Gephi to filter and process the data. Social Network Analysis (SNA) with Crawling Data was applied to determine user responses. The findings reveal the patterns of user interactions within the Lazada Marketplace, specifically in relation to vouchers, cashbacks, and flash sales. Furthermore, the study identifies the user response trends between 2018-2019 and 2020-2021, highlighting the marketing promotional content that received the most and least responses. Notably, the results indicate a significant user response to "cashback" marketing promotional content in 2020-2021, while user engagement with such content in 2018-2019 was relatively low. This study contributes to a better understanding of user behavior in response to marketing strategies and provides implications for optimizing promotional content on e-commerce platforms. Highlights: User engagement patterns: This study examines the interactions of Lazada Marketplace users with marketing promotional content, shedding light on the dynamics of user responses and engagement. Cashback effectiveness: The research identifies the effectiveness of "cashback" marketing promotional content, revealing the extent to which users respond to such offers during different time periods. Implications for optimization: The findings have practical implications for e-commerce platforms, providing insights into optimizing promotional strategies and content to enhance user engagement and maximize marketing effectiveness. Keywords: User Responses, Marketing Promotional Content, Lazada Marketplace, Social Network Analysis, E-commerce Platforms